2001
DOI: 10.1038/sj.bjp.0704374
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood glucose and plasma insulin levels induced by bradykinin in anaesthetized rats

Abstract: 1 The in¯uence of bradykinin (BK) on blood glucose and plasma insulin levels was investigated in anaesthetized rats. 2 Blood glucose level was dose-dependently increased by intravenous infusion of BK. This eect of BK was enhanced by captopril, an inhibitor of angiotensin-converting enzyme (ACE). Des-Arg 9 -bradykinin (DABK), a kinin B 1 receptor agonist, did not modify blood glucose levels while the eect of BK was inhibited by Hoe-140, a kinin B 2 receptor antagonist. The eect of BK was reduced by the NO-synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
(53 reference statements)
1
7
1
Order By: Relevance
“…In the present study, we showed that the local administration of BK increased adrenal catecholamine secretion without any significant changes in the systemic parameters such as mean aortic pressure, heart rate, and circulating catecholamine levels in aortic blood. These observations are consistent with the view that the increasing effect of BK on catecholamine secretion resulted from its direct action on the adrenal medulla and not from secondary factors such as a reflex-induced increase in sympathetic outflow that can be observed under certain conditions in vivo (28).…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, we showed that the local administration of BK increased adrenal catecholamine secretion without any significant changes in the systemic parameters such as mean aortic pressure, heart rate, and circulating catecholamine levels in aortic blood. These observations are consistent with the view that the increasing effect of BK on catecholamine secretion resulted from its direct action on the adrenal medulla and not from secondary factors such as a reflex-induced increase in sympathetic outflow that can be observed under certain conditions in vivo (28).…”
Section: Discussionsupporting
confidence: 80%
“…Reports on the metabolic effects of captopril on oral glucose tolerance and insulin action in the literature are conflicting. Studies have shown that captopril enhanced the effects of bradykinin, which via a stimulation of B 2 receptors caused the release of NO and of prostanoids, which resulted in increased blood glucose levels and reduced plasma insulin levels [20]. However the results from this study showed that captopril had no effect on oral glucose tolerance and insulin levels, and plasma nitrate/nitrite levels in captopril-treated dogs was comparable with age-matched controls administered with water.…”
Section: Discussioncontrasting
confidence: 54%
“…The release of adrenaline increases blood glucose and simultaneously inhibits insulin secretion. Indeed, in rats treated with α-and β-adrenergic blockers, BK induced an increase in plasma level of insulin associated with a decrease in blood glucose [89].…”
Section: Release Of Insulin Induced By Bkmentioning
confidence: 98%
“…Moreover, as we have demonstrated [25], the administration of a glucose load in kininogendeficient rats induced a larger hyperglycemia but a smaller increase in plasma level of insulin than in normal rats. These latter observations led us to study the influence of intravenous administration of BK on blood glucose level and plasma insulin level [88,89]. Intravenous injection of BK did not induce any significant changes in these parameters during one hour, while hypotensive responses were easily elicited by bolus injection of this peptide.…”
Section: Release Of Insulin Induced By Bkmentioning
confidence: 99%